Prediction and analysis of residential house price using a flexible spatiotemporal model - Lu Wang; Guangxing Wang; Huan Yu; Fei Wang (Journal of Applied Economics, 2022)
House price prediction has traditionally been approached using linear or spatial linear hedonic models and focused on big cities. In this study, we developed a flexible spatiotemporal model (FSTM) to explore the spatiotemporal characteristics of the residential house price and the impact factors in middle-small cities. The FSTM integrated both spatial and temporal components of the residential house price, accounted for its spatiotemporal characteristics, and reproduced its spatial variability and temporal trends. The results showed that the governmental policy had a significant influence on the house price and led to the characteristics being different from those in big cities. The significant factors also included the density of roads, the density of banks, density of supermarkets, the area used by public and user shared area within a building. This study implied that FSTM provided the potential for spatiotemporal prediction of the residential house price in the middle-small cities.
Keywords: 330; Driving factors; middle-small city; residential house price; Shunde district; spatiotemporal modeling; urbanization